2020
DOI: 10.1590/1806-93042020000200013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on the measurement properties of the Brazilian Portuguese language version of the International Consultation on Incontinence Questionnaire Female Sexual Matters Associated with Lower Urinary Tract Symptoms Module (ICIQ-FLUTSsex)

Abstract: Objectives: to assess internal consistency and reliability in providing a Portuguese version of the International Consultation on Incontinence Questionnaire Female Sexual Matters Associated with Lower Urinary Tract Symptoms Module (ICIQ-FLUTSsex). Methods: a validation study was conducted by applying questionnaires for 56 women over 18 years old with active sexual life and presenting urinary incontinence, excluding those who had urinary infection in the past 6 months. Three questionnaires were used, one for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Some women may experience pain or discomfort in the vaginal area, besides their worries about urine loss [ 25 ]. Based on the study by Andrade et al ., the ICIQ-FLUTSex is a valid and easy-to-use tool for assessing sexual dysfunction in women who complain of urinary incontinence [ 26 ]. The results of the ICIQ-FLUTSex in this study showed that the total mean score of the ICIQ-FLUTSex improved after 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some women may experience pain or discomfort in the vaginal area, besides their worries about urine loss [ 25 ]. Based on the study by Andrade et al ., the ICIQ-FLUTSex is a valid and easy-to-use tool for assessing sexual dysfunction in women who complain of urinary incontinence [ 26 ]. The results of the ICIQ-FLUTSex in this study showed that the total mean score of the ICIQ-FLUTSex improved after 5 years.…”
Section: Discussionmentioning
confidence: 99%